Measurement of inclusive J/ψ polarization in p+p collisions at √s=200 GeV by the STAR experiment - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert; Weidenkaff, Philipp (Physical review, 2020)
We report on new measurements of inclusive J/ψ polarization at midrapidity in p+p collisions at √s=200 GeV by the STAR experiment at the Relativistic Heavy Ion Collider. The polarization parameters, λθ, λϕ, and λθϕ, are measured as a function of transverse momentum (pT) in both the helicity and Collins-Soper (CS) reference frames within pT<10 GeV/c. Except for λθ in the CS frame at the highest measured pT, all three polarization parameters are consistent with 0 in both reference frames without any strong pT dependence. Several model calculations are compared with data, and the one using the Color Glass Condensate effective field theory coupled with nonrelativistic QCD gives the best overall description of the experimental results, even though other models cannot be ruled out due to experimental uncertainties.